PERKAWINAN SIMSON DALAM HAKIM-HAKIM 14:1-4: IMPLEMENTASINYA DALAM PEMBINAAN PRANIKAH DI LINGKUNGAN GEREJA BATAK - Ana Budi Kristiani (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2023)
Abstract:             This study aims to analyze the story of Samson's marriage in Judges 14:1-4 and identify its implications for premarital formation in the Batak Church environment. The story of Samson's marriage is important because it provides valuable insights into marriage and the principles associated with a successful marriage relationship. This study used qualitative research methods, in the research conducted, a Biblical research approach and a case study approach on premarital coaching in the Batak Church environment were used.It was found that children involve their parents when determining their choice of life partner. Parents provide guidance to children to choose friends who are like-minded. Then God is sovereign over the decision to choose a life partner that has been taken. Premarital material is based on the Word of God. The Batak culture of marriage is still respected by prioritizing the perspective of God's Word. Premarital coaching is given for children and parents and the Batak Church can do premarital coaching well according to the truth of God's Word.The implementation of the story of Samson's marriage in premarital coaching within the Batak Church is the importance of premarital coaching in building a solid foundation for marriage based on the principles of trust, loyalty, and commitment to God and one's spouse. This research provides a valuable contribution in the context of premarital coaching in the Batak Church environment by exploring the wisdom and lessons that can be drawn from the story of Samson's marriage. Through a deeper understanding of the values contained in this story, it is hoped that it can prepare prospective husband and wife to build a healthy and successful marriage relationship.Keywords: Samson's Marriage, Premarital Coaching, Batak Church